Association Analysis of Grain-setting Rates in Apical and Basal Spikelets in Bread Wheat (Triticum aestivum L.) - Guo, Jie; Zhang, Yong; Shi, Weiping; Zhang, Boqiao; Zhang, Jingjuan; Xu, Yanhao; Cheng, Xiaoming; Cheng, Kai; Zhang, Xueyong; Hao, Chenyang; Cheng, Shunhe (Frontiers in Plant Science, 2015)
The rates of grain-setting in apical and basal spikelets in wheat directly affects the kernel number per spike. In this study, 220 wheat lines from 18 Chinese provinces and five foreign countries were used as a natural population. Phenotypic analysis showed differences in grain-setting rates between apical and basal spikelets. The broad-sense heritability of grain-setting rate in apical spikelets (18.7-21.0%) was higher than that for basal spikelets (9.4-16.4%). Significant correlations were found between kernel number per spike and grain numbers in apical (R2=0.40-0.45, P＜0.01) and basal (R2=0.41-0.56, P＜0.01) spikelets. Seventy two of 106 SSR markers were associated with grain setting, 32 for apical spikelets and 34 for basal spikelets. The SSR loci were located in 17 chromosomes, except 3A, 3D, 4A and 7D, and explained 3.7-22.9% of the phenotypic variance. Four markers, Xcfa2153-1A202, Xgwm186-5A118, Xgwm156-3B319 and Xgwm537-7B210, showed the largest effects on grain numbers in the apical and basal spikelets. High grain numbers in the apical and basal spikelets were associated with elite alleles. Ningmai 9, Ning 0569 and Yangmai 18 with high grain-setting rated carried larger numbers of favorable alleles. Comparison of grain numbers in basal and apical spikelets of 35 Yangmai and Ningmai lines indicated that the Ningmai lines had better grain-setting rates (mean 21.4) than the Yangmai lines (16.5).